Transformation and Differentiation of Henstock-Wiener Integrals - Boonpogkring, Varayu (Archīum Ateneo, 2017)
In this paper, transformation and differentiation of Henstock-Wiener integrals are discussed. The approach is by Riemann sums. The idea is more transparent than that of classical Wiener integral.